Molecular and biochemical mechanisms of mitochondrial dysfunction in spontaneously hypertensive rats - Nahorna, E. A.; Chekman, I. S.; Belenichev, I. F.; Kolesnik, Yu. M.; Abramov, A. V.; Gorchakova, N. A.; Levich, S. V.; Нагорна, О. А.; Чекман, І. С.; Бєленічев, Ігор Федорович; Колесник, Юрій Михайлович; Абрамов, Андрій Володимирович; et al. (Hikari Ltd, 2016)
Objective: In conditions of hypertension, ATP synthesis can be violated that can lead to the development of energy deficit of cardiomyocytes. One of the reasons of such energy deficit could be mitochondrial dysfunction. Aim of this work was study of molecular and biochemical mechanisms of mitochondrial dysfunction in spontaneously hypertensive rats.
Keywords: Hypertension; heat shock proteins; mitochondrial dysfunction